2016
DOI: 10.1111/cpr.12283
|View full text |Cite|
|
Sign up to set email alerts
|

Sevoflurane represses the self‐renewal ability by regulating miR‐7a,7b/Klf4 signalling pathway in mouse embryonic stem cells

Abstract: Sevoflurane is a frequently-used clinical inhalational anaesthetic and can cause toxicity to embryos during foetal development. Embryonic stem cells (ESCs) are derived from the inner cell mass of blastospheres and can be used as a useful model of early development. Here, we found that sevoflurane significantly influenced self-renewal ability of mESCs on stemness maintenance and cell proliferation. The cell cycle was arrested via G1 phase delay. We further found that sevoflurane upregulated expression of miR-7a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…To verify our hypothesis, we further tested the change in other cell cycle parameters, including G1-, M-, and G2-phases. In a recent study, sevoflurane was reported to delay G1-phase and lead to cell cycle arrest in embryonic stem cells [ 43 ]. However, in our study of Ccnd1 labeling, the G1-phase of neural progenitors was not affected by prenatal sevoflurane exposure (Figures 6(b) , 6(c) , and 6(d) ).…”
Section: Discussionmentioning
confidence: 99%
“…To verify our hypothesis, we further tested the change in other cell cycle parameters, including G1-, M-, and G2-phases. In a recent study, sevoflurane was reported to delay G1-phase and lead to cell cycle arrest in embryonic stem cells [ 43 ]. However, in our study of Ccnd1 labeling, the G1-phase of neural progenitors was not affected by prenatal sevoflurane exposure (Figures 6(b) , 6(c) , and 6(d) ).…”
Section: Discussionmentioning
confidence: 99%
“…To mimic the conditions of anaesthesia by sevoflurane in vitro , the low glucose Dulbecco's modified Eagle's medium used for hippocampal neuron cultures was replaced with glucose‐free neurobasal medium supplemented with 1% B27 and 2.78 mmol/L glucose according to a previous study (Wang et al . ). The cells were maintained at 37°C with 5% CO 2 under induction with 4% sevoflurane for 6 h with/without treatment with RSG (5 μM).…”
Section: Methodsmentioning
confidence: 97%
“…They principally act as post-transcriptional gene regulators by binding to complementary sequences of target mRNAs, which leads to mRNA silencing via the inhibition of translation or destabilization of the mRNAs (15,16). miRs are expressed in response to particular conditions including exposure to anesthetic agents such as sevoflurane (12,17). Thousands of miR species have been identified, sequenced and characterized; however, their functional roles have yet to be clarified, as one miR may regulate the expression of a number of genes, including other gene regulators.…”
Section: Introductionmentioning
confidence: 99%